Pertanggungjawaban Perbankan Sebagai Korporasi Atas Penggelapan Dana Nasabah yang Dilakukan oleh Pegawai Bank - Suci Sulistiawati; Elsa Rina Maya Toule; Margie Gladies Sopacua (Faculty of Law, Universitas Pattimura, 2022)
Introduction: This article examines the judges' considerations in imposing criminal penalties against defendants who commit banking crimes under Article 49 paragraph (1) letters a and b of the Law of the Republic of Indonesia Number 10 of 1998 in conjunction with Article 64 paragraph (1) of the Criminal Code in the Supreme Court Decision Number 470/pi.B/2021/PN.AMB with the problem of fraud mode. Purposes of the Research: This study aims to analyze and explain the process of law enforcement for criminal acts in the embezzlement of customer funds by bank employees at PT.Bank BRI Ambn branch. Methods of the Research: The type of research used is legal research